Language Change The Case of Baghdadi Arabic After the American Occupation of Iraq in 2003 (Journal of the College of Basic Education, 2022)
This paper tackles language change in general, and changes in the Baghdadi Arabic Variety in particular. The study focuses on the changes that have taken place after the 8-years American occupation of Iraq (2003-2011). The method used for this study is the Apparent-time study approach, which is a synchronic method pioneered by Labov, that focuses on changes in terms of frequency of change (increase, decrease, or innovations) during a specific period of time. The American occupation of Iraq has caused many changes in the Baghdadi Arabic Variety ,and in the other varieties as well .The reason why focus in this paper is on the Baghdadi Arabic Variety is the fact that it is spoken by the majority of Iraqis, especially in the middle and south of Iraq. The main changes were found to be in the area of vocabulary, as many new expressions appeared and others diminished as a result of the new socio-political changes in the community in that period.